PENGARUH TEKNOLOGI INFORMASI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA INSTANSI PEMERINTAH - MZ, Era Inziaj; Yuliarti, Norita Citra; Aulin, Gardina (Fakultas Ekonomi dan Bisnis, 2023)
Situbondo Regency, which is located in Situbondo City at the easternmost tip of East Java Province, was established in 1972 and adopted the motto